Polyunsaturated fatty acids as a potential preventive and therapeutic intervention for metabolic dysfunction–associated steatotic liver disease and its progression to hepatocellular carcinoma - Kouti, Thomai; Christodoulou, Panayiota; Christodoulides, Stephanos; Protopapa, Foula; Michaeloudes, Charalambos; Farazi, Paraskevi A. (Frontiers in Nutrition, 2026)
Metabolic dysfunction–associated steatotic liver disease (MASLD) is currently the leading cause of chronic liver disease worldwide and a major cause of hepatocellular carcinoma (HCC), a cancer with poor prognosis. Considering the immense public health impact of MASLD and MASLD-HCC, preventive and more effective management strategies for these diseases are urgently needed. Polyunsaturated fatty acids (PUFAs) appear to improve liver health through modulation of lipid metabolism, inflammation and oxidative stress and therefore could influence MASLD and MASLD-HCC progression. To this end, this review discusses the role of PUFAs, more specifically n-3 and n-6, in MASLD and MASLD-HCC, by critically reviewing evidence from human clinical and observational studies, and experimental models. Human observational and clinical trial studies collectively suggest a beneficial effect of PUFAs in the prevention of MASLD and MASLD-HCC. Evidence in animal models indicate that n-3 PUFA supplementation suppresses the development of MASLD by preventing liver steatosis, inflammation, and fibrosis. These effects are mediated through a shift in lipid metabolism from lipogenesis toward lipolysis and fatty acid oxidation, inhibition of key inflammatory pathways and antioxidant effects. There is evidence from a small number of animal model studies showing a reduction in PUFA levels during MASLD progression to HCC, and a protective effect of n-3 PUFA supplementation against liver tumorigenesis. However, the evidence on the molecular mechanisms mediating this effect is very sparse. The evidence reported in this review suggests consideration of PUFAs, and particularly n-3 PUFAs, as potential preventive modalities for MASLD-HCC and for control of established MASLD-HCC in combination with existing therapies, albeit in a microenvironment context-dependent manner. Finally, the review highlights key gaps in the literature and suggests potential research opportunities to delineate the role of PUFAs in MASLD-HCC.